Bulk and Surface Electronic Properties of Inorganic Materials: Tools to Guide Cellular Behavior. Issue 9 (20th July 2018) - Snyder, Patrick J.; Reddy, Pramod; Kirste, Ronny; Collazo, Ramon; Ivanisevic, Albena
Abstract: Classical concepts associated with the electronic properties of inorganic materials in the context of conditions used in biointerface studies are summarized. Electronic properties provide unique ways for stimulating a variety of biological systems; however, here the major focus is on mammallian cells. An additional focus is placed on bulk and electronic properties prior to chemical functionalization of inorganic materials. Representative studies, challenges, and opportunities toward utilization of charge, conductivity, photoconductivity, polarity, and piezoelectricity‐dependent mamallian cell interfaces are highlighted. Abstract : The roles of surface and bulk charge, conductivity, photoconductivity, polarity, and piezoelectricity in the construction of biointerfaces from inorganic materials are reviewed. Representative bioelectonic devices for bioinformatics, sensing, cell stimulation and therapeutics are summarized.